Forecasting quantitative characteristics of officially registered HIV-infected persons in the region - Гече, Федір Елемирович; Мулеса, Оксана Юріївна; Миронюк, Іван Святославович; Вашкеба, Михайло Михайлович (Technology audit and production reserves, 2015)
The task of predicting quantitative characteristics of officially registered HIV-positive persons in the region occurs during the planning of public social and medical programs which by their nature programs of providing various services (medical, social, psychological, etc.) to target group of populations. Because these programs are developed and approved by both the national and regional level for a long period (five years), while planning measures provide key services is the availability of information on the expected number of users of these services for the period of the program. The problem of forecasting the quantitative characteristics of officially registered HIV-positive persons in the region is considered as the problem of forecasting based on time series. The features of the problem solving by methods of autoregression, Winters, least squares with weights, linear and quadratic model Brown are analyzed. For each method it is noted feature of its application and guidelines. It is proposed to calculate the predicted values of quantitative characteristics of the target group of people using synthesized forecasting scheme based on basic models. To solve the problem it is made specific calculation, during which stipulates that the slightest error of prediction of quantitative characteristics of the target group of individuals achieved through the use of synthetic schemes. Predicted values of basic quantitative characteristics of officially registered HIV-infected persons in Zakarpattya region in the period from 2015 to 2019 are calculated. Quantitative characteristics that calculated in the study can be used in planning activities to provide services to people living with HIV in the implementation of state and national programs in Ukraine aimed at countering HIV/AIDS.